Polymerization of ethylene by the tris(pyrazolyl)borate titanium(IV) compound immobilized on MAO-modified silicas - Gil, M. P.; dos Santos, JHZ; Casagrande, O. L. (Elsevier B.V., 2004)
The immobilization of soluble catalyst {Tp(Ms)}TiCl3 (Tp(Ms*)HB(3-mesityl-pyrazolyl)(2)(5-mesityl-pyrazolyl)(-)) on silica and MAO-modified silicas containing 4.0, 8.0 and 23.0 wt.% Al/SiO2 yields active supported catalysts for ethylene polymerization. Among the supported catalysts studied by XRF spectroscopy, higher titanium content was obtained using MAO-modified silica containing 8.0 wt.% Al/SiO2 as support. For the ethylene polymerization reactions carried out in hexane at 60degreesC using a combination of triisobutylaluminum (TiBA) and methylaluminoxane (MAO) (1:1), the activities varied between 24.4 and 113.5 kg of PE/mol [Ti] h. The highest activity is reached using MAO-modified silica containing 4.0 wt.% Al/SiO2 as support. The viscosity-average molecular weights ((M) over bar (v)) of the PE's produced with the supported catalysts varying from 1.44 to 9.94 x 10(5) g/mol with melting temperatures in the range of 125-140degreesC. The use of other Lewis acid cocatalysts, including TiBA, diethylaluminium chloride (DEAC), and trimethylaluminum (TMA) resulted also in the formation of active catalysts for ethylene polymerization. However, the activities are lower than that one using a combination of TiBA and MAO. The viscosity-average molecular weights (R,) of PE's are influenced by varying the cocatalysts as well as the Al/Ti molar ratio. The supported catalyst generated in situ under ethylene atmosphere is roughly four times more active than supported one containing 4.0 wt.% Al/SiO2. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: tris(pyrazolyl)borate titanium complex; supported catalysts; polyethylene